Dampak Kredit Modal Terhadap Peningkatan Usaha Pedagang Kecil di Pasar Sentral Kota Gorontalo. - Abdul Latif; Ayatullah Ayatullah (Al-Buhuts, 2018)
The purpose of this study is to determine the extent of the impact generated by the capital loan to increase small trader business in the central market of Gorontalo city. This research data is obtained through several samples of small traders in the central market of Gorontalo city. Data collection techniques used are interviews, observations and documentation and then the data collected and then analyzed by using inductive thinking analysis that describes or explains and assesses related data related to the impact of business capital credit on business improvement in the central market of Gorontalo city. From the result of the research, it is found that credit indeed has an impact on the improvement of small traders business in the central market of Gorontalo city, it is indicated by the fact that before getting a small capital loan loan it is difficult to increase the commodity sold or the product sold when they have received the credit before they Easy to get additional goods